2011
DOI: 10.1097/pas.0b013e3181ffd8ab
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Fibroblastic and Myofibroblastic Proliferation of the Vulva (Cyclist's Nodule)

Abstract: Perineal nodules occurring in male cyclists are reported in the literature, although the histologic features are not extensively documented. There has been little description of similar lesions in the female population. We describe 4 cases in which a vulval nodule or swelling developed in competitive female cyclists aged 15 to 45 years. The lesions were unilateral and occurred on the right or left labium majus (2 cases each). The histologic features were similar in all cases and consisted of a haphazard admixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 17 publications
0
32
0
1
Order By: Relevance
“…2,3 Perineal nodules are not exclusive to men; female cases have also been reported. 1,4 The appearance of the nodules is stereotypical. The lesion can be unilateral or bilateral, be situated beneath the scrotum or on the labia majora, and measure between 2 and 5 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Perineal nodules are not exclusive to men; female cases have also been reported. 1,4 The appearance of the nodules is stereotypical. The lesion can be unilateral or bilateral, be situated beneath the scrotum or on the labia majora, and measure between 2 and 5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, perineal nodular induration is a little known complication, referred to using a variety of terms including perineal nodular induration of the cyclist, ischiatic hygroma, accessory testicle, third testicle, or biker's nodule. In the following study, we report on three cases of perineal nodular induration in cyclotourists.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 It is more commonly seen in males, but recently, five female cases have been reported. 9,10 Its latency period varies from a few weeks to one year. Although the nodule in our case was mobile, most reports state that it is fixed to the soft tissue or ischial tuberosity, has a fibrous to elastic consistency, and is covered by normal skin.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,7 Similarly, it has been reported that these repeated microtrauma could also result in conjunctive tissue damages known as 'perineal nodular induration' or 'cyclist nodule'. 7,8 However, the histological aspect is characterized by a vulvar fibroblastic and myofibroblastic proliferation, 8 whereas bicyclist's vulva seems to have a normal skin biopsy.…”
Section: Dear Editormentioning
confidence: 99%